Investigating the Validity and Reliability of WTC Construct In L2 Arabic: A Case Study - Fahri, Muhamad; Arrahman, Fajar Pinastia; Albantani, Azkia Muharom; Mahfuzo, Muhammad Rizal; Muslimin, Muhamad Ihwanul (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
The main goal of learning Arabic is to develop practical linguistic skills among learners centered around the concept of willingness to communicate (WTC). WTC refers to learners' strong desire and readiness to speak in specific contexts or situations. A critical challenge is how to accurately measure WTC in Arabic language learning using a valid and reliable instrument. Understanding WTC is crucial as it indicates learners' motivation to use Arabic, enhances their speaking proficiency, and creates a supportive linguistic environment. Research on WTC in Arabic language learning is currently limited, necessitating further exploration in this area. Consequently, this study aims to develop a valid and reliable WTC measurement instrument for Arabic language learners using a quantitative approach, incorporating both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) methods. The participants for this research are 204 Arabic language learners, and a survey was utilized for data collection. The WTC instrument employed in this study is an adaptation of existing instruments, modified to align with the context of Arabic language learning and the specific conditions of Indonesian learners. The findings reveal that the WTC construct has yielded valid and reliable items that can be used to measure WTC among learners in Arabic language learning. Furthermore, there are three main dimensions within this construct, namely, the context of online, classroom, and offline. Thus, it is hoped that the WTC construct developed can be utilized to measure aspects of WTC among Arabic language learners, thereby enabling the determination of further steps in realizing linguistic behaviors